2010
DOI: 10.1007/s00134-010-1787-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnic acidosis in ventilator-induced lung injury

Abstract: Hypercapnia provided consistent and biologically plausible in vivo protection against VILI, but elevated lung tissue levels of nitro-tyrosine as previously described in sepsis. Clinicians and those designing clinical trials need to be aware of the potential for detrimental effects when using hypercapnia in order to balance benefits versus harm with this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 52 publications
2
34
0
1
Order By: Relevance
“…However, postoperative hypercapnia did not result in severe perioperative outcomes. In accordance with previous publications, 27 we also believed that temporary hypercapnia was permissible, and the safety of the operation was not compromised in our study.…”
Section: Discussionsupporting
confidence: 92%
“…However, postoperative hypercapnia did not result in severe perioperative outcomes. In accordance with previous publications, 27 we also believed that temporary hypercapnia was permissible, and the safety of the operation was not compromised in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Permissive hypercapnia and permissive hypoxemia should be employed when clinically indicated, to minimize exposure to toxic ventilatory support. 74,[82][83][84][85][86] The target P aO 2 , S pO 2 , and P aCO 2 are likely to differ between patients and within an individual patient over time, based on the degree of ventilatory support the patient requires (ie, risk of ventilatorinduced lung injury).…”
Section: Management Algorithmmentioning
confidence: 99%
“…There are a number of studies that have actually shown beneficial effects of permissive hypercapnia in that it may have the potential to attenuate lung injury. [51][52][53][54] Some have even suggested that hypercapneic acidosis could be therapeutic as opposed to permissive. 55 However, the degree of permissive hypercapnia that can be used safely during low V T ventilation is unclear, but it may be that a mild acidosis should be tolerated to enable the use of lower V T values.…”
mentioning
confidence: 99%